Differential penalization of murder. A sociological examination of the Argentinean case // Penalización diferencial del asesinato. Una aproximación sociológica del caso argentino - Lassalle, Martina (Espacio Abierto, 2020)
Abstract Differential administration of punishment is a relevant political and social issue for it is a clear indicator of the criminal system’s selectivity. This relevance is even greater when referring to murder: considered the most serious of all crimes, its punishment entails moral concerns to every society. Paradoxically, this problem has not been very much investigated in Argentina and in Latin America in general, even when it is one of the regions with the highest homicide rates of the world. The present article seeks to provide some empirical analyses on differential penalization of murder in contemporary Argentina in order to contribute to this field of study. Using data from the most recent penitentiary census of the country (corresponding to 2018) we examine differential administration of punishment regarding the offender’s gender, age, nationality, social class and criminal career. We analyse to what extent these variables impact in the probability of getting lifelong imprisonment and in the length of the sentences imposed by judges. Our study shows that women are more likely to get harsher punishments than men, and that defendants with higher levels of education have been punished more severely than those with no studies at all. Resumen La administración diferencial del castigo es una problemática política y social relevante dado que es un claro indicador de la selectividad del sistema penal. Esta relevancia es aún mayor cuando nos referimos al asesinato: considerado el más grave de todos los crímenes, su castigo entraña inquietudes morales a toda sociedad. Paradójicamente, esta problemática ha sido poco investigada en Argentina y en Latinoamérica en general, aun cuando se trata de una región con las tasas de homicidio más altas del mundo. El presente artículo se propone analizar la penalización diferencial del homicidio en Argentina, para así contribuir a este campo de estudios. Utilizando los datos del último censo penitenciario del país, correspondiente al año 2018, examinamos la administración diferencial del castigo en relación al género, la edad, la nacionalidad, la clase social y carrera criminal de los condenados por este delito. Buscamos analizar en qué medida estas variables influyen en la probabilidad de obtener sentencias perpetuas y en el monto de las condenas impuestas por los jueces. Nuestro estudio muestra que las mujeres tienen más probabilidades que los hombres de obtener condenas perpetuas, y que los acusados con estudios secundarios completos han recibido penas más severas que los acusados con niveles educativos más bajos.